Stimulants économiques et utilisation des services médicaux - Contandriopoulos, André-Pierre (L'Actualité économique, 1980)
AbstractHaving demonstrated that the traditional economic model of the market cannot be used in its present form to understand what is happening in the field of medical services, a presentation will be made of the factors affecting the behavior of physicians as purveyors of services, thus showing the importance of analyzing the influence of economic incentives on physician behavior. The analysis consists of measuring the change in the practice profiles of physicians from 1971 to 1973, and evaluating the influence of the fee schedule on this change. This research allows us to show that the personal characterictics of physicians, the characteristics associated with the organization of their practice and the area in which they practise are only very slightly related to the changes in the mix of the medical services produced by physicians; that the change in the profile of practice cannot be associated with changes in the populations' needs, and that the financial incentives incorporated in the fee schedule have been found to be mainly responsible for the shifts observed in the profiles of practice. We conclude by showing how these results are compatible with the hypothesis that physicians can influence demand for medical services.